Estudo da soldagem por eletrodo revestido utilizando o aço 308L e a técnica cold wire - Costa, Rafael Cortinas de Castro (2017)
Carbon steel coatings with stainless steel have been widely used in many chemical, petrochemical and nuclear products. The ability to join two different metals in both properties and cost allows the creation of parts that support hostile environments at a lower cost. SMAW process welding has an advantage due to the ease of use of the equipment, as well as having excellent results both in the production and in the repair of equipment. Thus, the objective of the work is to analyze the result of this welding by electrode coated with 308L steel on carbon steel, added to pre-machining in the test body with addition of an electrode of 308L steel in the bevel in order to increase the deposition rate of the material. The welding analyzes were performed through the penetrating liquid, microhardness and macroscopic analyzes. Through them it was possible to verify that with the welding currents of 60A and 80A there was no complete fusion, although the dilution was low. While with the welding current at 100A there was total melting of the material, but in compensation the dilution was greater.